Caching strategy based on transmission delay for D2D cooperative edge caching system - Yan CAI; Fan WU; Hongbo ZHU (Tongxin xuebao)
To meet the requirements of 5G system with low delay and high reliability, for a single-caching D2D cooperative edge caching system, an optimization of the caching strategy based on transmission delay was proposed.The dynamic distributions of requesting users and idle users were modeled as the independent homogeneous poisson point process (HPPP) utilizing the stochastic geometry theory.Comprehensively considering the content popularity, user location information, device transmission power and interference, the relationship between the average transmission delay of user and the cache probability distribution was derived.Taking the average transmission delay as the objective function, the optimization problem was established, and a low complexity iterative algorithm was proposed to obtain the cache strategy with sub-optimal average transmission delay.Simulation results demonstrate that the proposed optimization cache strategy is superior to several common cache strategies in terms of transmission delay.